Hyaloraphidium curvatum is not a green alga but a lower fungus; Amoebidium parasiticum is not a fungus, but a member of the DRIPs - Ustinova, Iana; Krienitz, Lothar; Huß, Volker (Protist, 2000)
The unicellular heterotrophic protist Hyaloraphidium is classified with a family of green algae, the Ankistrodesmaceae. The only species that exists in pure culture and that is available for taxonomic studies is H. curvature. Comparative18S ribosomal RNA sequence analyses showed that H. curvature belongs to the fungi rather than to the algae. Within the fungi, H. curvatrum preferentially clustered with Chytridiomycetes. Unlike Chytridiomycetes, H. curvature propagates by autosporulation, and the presence of flagella has never been reported. Transmission electron microscopy indicated that H. curvature in some respects resembles Chytridiomycetes, but no elements of a flagetlar apparatus were detected. The habitus of H. curvature is unlike that of other fungi except the trichomycete Amoebidium parasiticum. The cell wall sugar composition of H. curvature was unique, but to some extent resembled that of A. parasiticum. However, H. curvature and A. parasiticum are not closely related to each other according to 18S rRNA sequence data. Moreover, A. parasiticum clustered with protistan animals, the Mesomycetozoa (DRIPs). Combined molecular, ultrastructural and chemical data do not allow assignment of H. curvature to any recognized clade of fungi. This suggests that H. curvature may represent an independent evolutionary lineage within the fung